2013
DOI: 10.3168/jds.2013-6552
|View full text |Cite
|
Sign up to set email alerts
|

Transport phenomena in a model cheese: The influence of the charge and shape of solutes on diffusion

Abstract: During cheese ripening, microorganisms grow as immobilized colonies, metabolizing substrates present in the matrix and generating products from enzymatic reactions. Local factors that limit the rates of diffusion, either within the general cheese matrix or near the colonies, may influence the metabolic activity of the bacteria during ripening, affecting the final quality of the cheese. The objective of this study was to determine the diffusion coefficients of solutes as a function of their different physicoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
57
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 66 publications
(72 reference statements)
4
57
0
Order By: Relevance
“…Dextran macromolecules from 4 to 2000 kDa could diffuse through the model cheese, even if their diffusion coefficients within the protein network were reduced relative to that in water. Silva et al (2013) also observed that the decrease of the diffusion coefficients of dextran molecules as function of their molecular weight could be modeled by a power law relationship with an exponent of À0.5. It was deduced from these results that the pore sizes of the model cheese were much larger than the diameter of the largest dextran molecule studied.…”
Section: Introductionmentioning
confidence: 88%
See 4 more Smart Citations
“…Dextran macromolecules from 4 to 2000 kDa could diffuse through the model cheese, even if their diffusion coefficients within the protein network were reduced relative to that in water. Silva et al (2013) also observed that the decrease of the diffusion coefficients of dextran molecules as function of their molecular weight could be modeled by a power law relationship with an exponent of À0.5. It was deduced from these results that the pore sizes of the model cheese were much larger than the diameter of the largest dextran molecule studied.…”
Section: Introductionmentioning
confidence: 88%
“…These were tagged with fluorescein isothiocyanate conjugate and denoted as D10, D20, D40, D70, D150, D250, and D500 according to their nominal average MW. Diffusion coefficients of these FITC-dextrans in milk aqueous phase (permeate from the milk ultrafiltration) (D aq ) have been previously determined using the FRAP procedure at 19°C (Silva et al, 2013). This solution, mainly composed of water, lactose and minerals, was used to represent the continuous aqueous phase filling the voids of cheeses.…”
Section: Diffusing Macromoleculesmentioning
confidence: 99%
See 3 more Smart Citations